Determination of the Effect of Psychoeducation Programme Applied to Cancer Patients on Sleep Quality and Perceived Stress Levels - Musa Paça; Veysel Kaplan (Social Medicine)
Objective. This study is conducted to determine the effect of a psycho education program me applied to cancer patients on their sleep quality and perceived stress levels.  Method and Material. The study is an experimental type with pre-test post-test and an experimental control group, and the sample of the study consists of patients receiving inpatient or outpatient treatment in a training and research hospital between 01.04.2023 and 25.08.2023. Research data are obtained by using a Personal Information Form, Perceived Stress Scale (PSS) and Richard-Campbell Sleep Scale (RCS). A total of 32 patients, including 16 experimental and 16 control groups, participated in the study. Results. As a result of the analyses, it is determined that 56.3% of the experimental group are female, 81.3% are married, and 25% are diagnosed with GI tract cancer. It is determined that the mean pre-test score of the experimental group in the study is 51.09 ± 11.56 and the mean post-test score is 58.65 ± 11.05, and the mean pre-test score of the ASQ is 47.5 ± 5.07 and the mean post-test score of the ASQ is 43.13 ± 4.77. After psycho education, it is found that the sleep quality of the individuals in the experimental group increased significantly (t= 5,736, p<0,001) and the perceived stress decreased (t= 6,143, p<0,001). Conclusion. Inline with the findings obtained in the results of the study, it is determined that the psycho education program me improved the sleep quality of the individuals and reduced the perceived stress level.